Kekuatan Hukum Mengikat Rekomendasi Inspektorat Kabupaten Maluku Barat Daya Terhadap Pengembalian Kerugian Keuangan Negara Oleh Kepala Desa - Daniel Adipura Romiwy; Jemmy Jefry Pietersz; Victor Juzuf Sedubun (LUTUR Law Journal, 2022)
Discretion by the village head of Kokwari which was reported by the community to the Inspectorate Board of Southwest Maluku Regency as a form of alleged corruption in the case of misuse of village funds. This research is a normative juridical research, and then examines and knows the answers to this problem through a concept approach, statutory approach and case approach, then from the results of the description conclusions and suggestions can be drawn. The results of this research and analysis of the problem use the concept of the Pancasila legal state and the concept of binding legal force, which are the initial framework for thinking about binding legal force. The results showed that the Recommendations of the Inspectorate of Southwest Maluku Regency regarding the return of state financial losses by the Kokwari Village Head have binding legal force, which lies in various normative provisions in a hierarchical manner so that they can guarantee and assess the quality or quality of each implementation of the work carried out by the Village Government on the management The Village Fund Budget is within the scope of the Regional Government of Southwest Maluku Regency, for this reason the Inspectorate Board of Southwest Maluku Regency issued a recommendation regarding the return of state financial losses by the Kokwari Village Head, of course, administrative legal consequences in terms of accountability that with the completion of the return of state financial losses carried out by the Kokwari Village Head cannot be prosecuted for criminal responsibility under Article 4 of Law Number 31 of 1999 in conjunction with Law Number 20 of 2001 concerning the Eradication of Corruption Crimes.